Pengaruh Promosi, Harga, Kualitas Layanan, Kualitas Produk Terhadap Kepuasan Pelanggan Shopee: Sebuah Kajian Konseptual - Ahyawa Aulia Khoirin Nisa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Shopee is an online shopping platform that provides a variety of sales products ranging from electronics, household equipment, clothing, accessories and fashion. In marketing activities, the factors that influence customer satisfaction are promotion, price, service quality and product quality. The aim of this research is that there is a research gap and various and inconsistent results that occur so the author wants to research further on this matter. The research will use quantitative methods and use the IBM Statistical Package for the Social Science (SPSS) Statistics program to calculate validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, regression analysis, coefficient of determination, F test, and t test.